(untitled) (Homiletic, 2025)
This article reflects on the introductory preaching course as a site of possibility for practices that promote diversity, equity, and inclusion (DEI). In the two segments of the 2022-23 Academy of Homiletics study that surveyed teaching attitudes and practices of its members, researchers observed some shifts toward more diverse representation of authors in the course readings (required, recommended, and additional bibliographic citations) from the first period to the second period, which varied by social location of the syllabus authors. Also of note in the syllabi are example sermons and course assignments that seek to address DEI concerns. The central question of this article addresses how the introductory preaching course serves as the primary gateway to students’ interaction with the field of homiletics and the challenges, opportunities, and options for diverse representation, equity, and inclusion, especially as it relates to the construction of the course syllabus. The article draws on examples from the anonymized syllabi submitted for the study and engages current studies in pedagogy and in theological education, particularly those which emphasize anti-colonialism and anti-racism, and offers recommendations for adding or enhancing commitments and practices for DEI.